Iron sulfide decorated ramie fiber-derived biochar for efficient Cr(VI) removal from water: Synergistic mechanisms of adsorption, reduction, and co-precipitation - Chengrui Shao; Luyao Gong; Liangxia Kong; Boyan Cui; Lifeng Xu; Xu Deng; Yuwei Deng; Qiang Li; Jun Wan; Yuxuan Ye; Fei Pan (Journal of Water Process Engineering, 2026)

Environmentally relevant concentrations of DCOIT impaired lifespan and healthspan in Caenorhabditis elegans - Xiaoyu Zhu; Yahui Shang; Heng Ni; Yuwei Wang; Chuang Ban; Zhenyan Cui; Sitong Dong; Yu Shi; Dajing Xia; Yihua Wu (Journal of Environmental Sciences, 2026)

Hulless barley β-glucan alleviates type 2 diabetes mellitus in BKS/db mice: Insights from gut microbiota remodeling and liver metabolomics profiling - Juan Bai; Cui Li; Qian Peng; Shunxin Xue; Xiaolong Lian; Xiaohua Yao; Kunlun Wu; Yuwei Wang; Guangxiang Luan (Food Bioscience, 2026)

Mechanical properties and stochastic damage constitutive model of the frozen soil-grout interface under low temperatures - Honghuan Cui; Zhiqiang Hu; Song Zhang; Yuan Li; Jian Cao; Yuwei Chen; Yong Liu; Liqun Zhang; Yanjie Ji (Transportation Geotechnics, 2026)

Overlooked role of submerged macrophytes in the seasonal persistence of odor-producing Pseudanabaena - Zhijie Cui; Changtao Yang; Limin Ma; Xiaoyan Gu; Xiaobing Shen; Bin Wan; Yuwei Tao; Yuting Sang; Yong Liu; Qinghui Huang (Journal of Environmental Sciences, 2026)

A data-driven life cycle assessment of battery swapping for electric two-wheelers: A multi-city operational perspective - Qian Zhang; Wei Liu; Xiaowei Cui; Xin Pan; Lu Chen; Wangqiu Liu; Yuwei Zhao; Liyao Wang; Mingxue Zhang; Lijun Ren; Zhaojie Cui (Sustainable Production and Consumption, 2026)

Structurally constrained hybrid modeling for cross-year prediction and mechanistic interpretation of marine biofouling evolution - Zhiqiang Cui; Haonan Huang; Yuanbei Li; Qiang Xu; Yuwei Hong; Mengting Jia (Ocean Engineering, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Determination of dissociation constants between single-protein and multicomponents by a multi-chamber membrane separation electrophoresis system as a complementary tool - Hai-Bo Shang; Yuwei Zhu; Yonglong Liu; Lei Yang; Yanying Qu; Meiyu Cui; Meihua Dong; Xiangfan Piao; Donghao Li (Analytica Chimica Acta, 2026)

Tripolyphosphate-enhanced Fe-C promotes O2 activation for bisphenol A removal: Roles of tripolyphosphate and dominant reactive oxygen species - Xiang Li; Mengke Zhang; Huajing Song; Qingge Cui; Yuwei Pan; Zhenglong Li; Wei Zou (Journal of Environmental Chemical Engineering, 2026)

Evaluation of agricultural and forestry waste barriers in mitigating soil salinization under simulated seawater intrusion: A long-term soil column study - Wenhan Liu; Yuwei Zhao; Yuzhao Cui; Kang Wang; Huitian Duan; Xiufeng Cao; Xiaowei Cui; Zhaojie Cui (Journal of Environmental Chemical Engineering, 2026)

Multi-source straw used as a resource can reduce environmental and economic burdens - Yuwei Zhao; Lu Chen; Wei Liu; Huiying Yang; Shuai Li; Xiaowei Cui; Zhaojie Cui (Environmental Impact Assessment Review, 2026)

Identification of photosynthetic pigment content-related genes in peanut (Arachis hypogaea L.) by GWAS and RNA-seq - Tingting Chen; Zijun Huang; Yuwei Cui; Jing Cao; Ruier Zeng; Yiyang Liu; Qunjie Zhang; Shubo Wan; Guowei Li; Lei Zhang (Theoretical and Applied Genetics, 2026)

Rapid and efficient inactivation of Pseudocohnilembus persalinus in aquaculture water using O3/H2O2 advanced oxidation technology - Yuwei Cui; Jingfeng Jia; Xiaojuan Shao; Wulong Jiang; Wenke Liu; Hua Wang; Ruijun Li; Zhongming Huo (Aquaculture International, 2026)

Spatiotemporal evolution and driving mechanisms of hazardous air pollutants and greenhouse gas emissions from China's copper industry - Lu Chen; Yuwei Zhao; Feng Han; Yuzhao Cui; Huiying Yang; Huitian Duan; Shuai Li; Xiaowei Cui; Wei Liu; Zhaojie Cui (Journal of Cleaner Production, 2026)

Corrigendum to “’Useful’ template synthesis of N-doped acicular hollow porous carbon/carbon-nanotubes for enhanced capture and selectivity of CO2” [Chemical Engineering Journal 361 (2019) 278–285/ WOS:000457096400029] - Xin He; Jing Liu; Yuwei Jiang; Muhammad Yaseen; Haoyu Guan; Jianhua Sun; Xuemin Cui; Dankui Liao; Zhangfa Tong (Chemical Engineering Journal, 2026)

Tree trunk disease mapping using hyperspectral LiDAR - Peilun Hu; Yuwei Chen; Wei Li; Huaguo Huang; Samuli Junttila; Shuanghui He; Yanan Zhao; Xiaoqi Cui; Mohammad Imangholiloo; Changhui Jiang; Jianxin Jia; Haibin Sun; et al. (Computers and Electronics in Agriculture, 2025)

Exploring spatiotemporal dynamics of urban flood socioeconomic exposure risk and driving factors under future precipitation change and urbanization scenarios - Wen Liu; Qi Feng; Yuwei Liang; Yanqiang Cui; Long Xu; Bernard A. Engel (Journal of Environmental Management, 2025)

Effect of heavy aromatic structures on particulates emission of GDI vehicles under WLTC and RDE conditions - Xin Zhang; Houzheng Wang; Jingyuan Li; Yuwei Wang; Hanzhengnan Yu; Shizhe Liu; Yu Liu; Mingyu Liu; Feng Yan; Yunong Cui (Fuel, 2025)

Floating-leaved and submerged macrophytes suppress filamentous cyanobacteria blooms and 2-MIB episodes in eutrophic shallow lakes - Zhijie Cui; Changtao Yang; Limin Ma; Xiaoyan Gu; Xiaobing Shen; Bin Wan; Yuwei Tao; Yuting Sang; Qinghui Huang (Journal of Hazardous Materials, 2025)

Bisphenols exposure at environmentally relevant dose promoted ovarian cancer progression and modulated tumor microenvironment through β-catenin/SPP1 axis - Sinan Xu; Xiaoyu Yuan; Yuwei Wang; Zhiqin Fu; Kelie Chen; Zhenyan Cui; Leting Xu; Honghe Zhang; Dajing Xia; Yihua Wu (Journal of Hazardous Materials, 2025)

Efficient adsorption of tetracycline by phytic acid modulated ramie fiber-derived porous carbon: Performance, mechanism, and application potential - Dongxinyu Chen; Yuwei Deng; Boyan Cui; Shou Mei; Lixi Xiao; Huo Zhou; Ziyi Zhan; Rongling Wang; Xuanyuan Pei; Qiang Li; Jun Wan; Yuxuan Ye; et al. (Journal of Water Process Engineering, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Unraveling the impacts of high solids content on hydrolysis and methane production of complex substrates through experimental and modeling approaches - Yuwei Niu; Yongmei Jiang; Liangcheng Yang; Yang Hu; Jiahao Cui; Fuqing Xu (Chemical Engineering Journal, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Life cycle environmental and economic assessment of Phosphogypsum utilization in China - Lu Chen; Xiaoyu Luan; Feng Han; Yuwei Zhao; Huiying Yang; Long Zhang; Yongquan Yin; Wei Liu; Zhaojie Cui (Resources, Conservation and Recycling, 2025)

Prenatal exposure to elevated ambient temperature may cause bronchopulmonary dysplasia: Evidence from twin pairs across China - Yuan Zheng; Xinqi Zhong; Wan Peng; Qijiong Zhu; Lv Wang; Changshun Xia; Yixiang Huang; Jiahong Xu; Zhiqing Chen; Yuwei Fan; Yiyu Lai; Qiliang Cui; et al. (Science of The Total Environment, 2024)

Environmentally relevant level of PFDA exacerbates intestinal inflammation by activating the cGAS/STING/NF-κB signaling pathway - Zhenyan Cui; Xiaoyu Yuan; Yuwei Wang; Zekun Liu; Xiaohong Fei; Kelie Chen; Han-Ming Shen; Yihua Wu; Dajing Xia (Science of The Total Environment, 2024)

Environmentally relevant concentrations of perfluorobutane sulfonate impair locomotion behaviors and healthspan by downregulating mitophagy in C. elegans - Yahui Shang; Kelie Chen; Heng Ni; Xiaoyu Zhu; Xiaoyu Yuan; Yuwei Wang; Xinxin Liu; Zhenyan Cui; Yuequn Niu; Yu Shi; Han Wu; Dajing Xia; et al. (Journal of Hazardous Materials, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Learning Improves Peripheral Vision Via Enhanced Cortico-Cortical Communications - Yuwei Cui; Xincheng Lu; MiYoung Kwon; Nihong Chen (Neuroscience Bulletin, 2024)

Form perception is a cognitive correlate of the relation between subitizing ability and math performance - Zhijun Cui; Yuwei Hu; Xinnan Wang; Chen Li; Zhengkui Liu; Zhanling Cui; Xinlin Zhou (Cognitive Processing, 2024)

New butanolide derivatives from the marine derived fungus Aspergillus terreus GZU-31-1 by chemical epigenetic manipulation - Yuwei Zhou; Xiaocong Chen; Yuqian Tang; Yena Liu; Zhongxiang Zhao; Hui Cui (Natural Product Research, 2024)

Soil erosion sensitivity and prediction for hilly areas of Hubei Province, China, using combined RUSLE and LSTM models - Yaodong Ping; Pei Tian; Li Luo; Yahui Guo; Yuwei Gong; Zhanliang Zhu; Yongsheng Cui; Lin Chen (Journal of Soils and Sediments, 2024)

Driving forces and recovery potential of the macrophyte decline in East Taihu Lake - Changtao Yang; Xiaobing Shen; Jianbin Wu; Xinyi Shi; Zhijie Cui; Yuwei Tao; Haiming Lu; Jianhua Li; Qinghui Huang (Journal of Environmental Management, 2023)

Development of genetic sex markers of zig-zag eel (Mastacembelus armatus) by a NGS method - Weijian Qin; Chong Han; Jinlin Yang; Zhide Yu; Yuwei Feng; Yuxin Wu; Baoyue Lu; Mingxiang Cui; Hu Shu (Aquaculture, 2023)

Low-dose BPA and its substitute BPS promote ovarian cancer cell stemness via a non-canonical PINK1/p53 mitophagic signaling - Xiaoyu Yuan; Kelie Chen; Fang Zheng; Sinan Xu; Yating Li; Yuwei Wang; Heng Ni; Fang Wang; Zhenyan Cui; Yuheng Qin; Dajing Xia; Yihua Wu (Journal of Hazardous Materials, 2023)

Terpenoids and other secondary metabolites produced by the Eutypella fungi and their bioactivities - Yuwei Zhou; Jingxin He; Hui Cui (Frontiers in Marine Science, 2022)
The fungi Eutypella could metabolize a myriad of natural products with unique structures and diverse bioactivities, which were deemed as key sources for lead compounds in drug discovery. Since the first research on the genus Eutypella in 2009, a myriad of secondary metabolites including terpenoids, alkaloids, and polyketides have been discovered in this genus, and most of them exhibited significant pharmacological activities. However, there are no systematic reviews that reported about the structures and bioactivities of Eutypella up to now. In this review, a total of 153 secondary metabolites and 42 references have been systematically summarized, and we found that the terpenoids (68.09%) and alkaloids (19.15%) were the new main components of this fungi, and the primary antiproliferative activity (64.89%) was mainly derived from the terpenoids and alkaloids. Thus, this review about the chemical diversity and biological activities of the metabolites from the fungus Eutypella provided a new perspective for the development of new drugs for pharmacologists.

RsmA3 modulates RpoS through the RetS‐Gac‐Rsm signalling pathway in response to H 2 O 2 stress in the phytopathogen Pseudomonas syringae - Xun Yu; Cui Meng; Xiaocheng Tan; Yuwei Su; Zhiping Cao; Tzann‐Shun Hwang; Lin Li (Environmental Microbiology, 2022)
Reactive oxygen species are a fatal challenge to the plant pathogenic bacterium Pseudomonas syringae . In this study, we reveal that the global regulatory protein RsmA3 from the RetS‐Gac/Rsm signalling pathway modulates RpoS in the early‐log growth phase in the P . syringae wild‐type strain MB03, thereby regulating oxidative tolerance to H 2 O 2 and ultimately affecting pathogenicity to the host plant. Following increased H 2 O 2 by external addition or endogenous induction by menadione, the resistance of the mutant strain Δ retS to H 2 O 2 is significantly enhanced due to rapid increases in the transcription of Rsm‐related non‐coding small RNAs (nc sRNAs), a sigma factor RpoS, and H 2 O 2 ‐detoxifying enzymes. Moreover, the Δ retS mutant is significantly less pathogenic in cucumber leaves. Seven Rsm‐related nc sRNAs (namely, rsmZ , rsmY and rsmX 1–5 ) show functional redundancy in the RetS‐Gac‐Rsm signalling pathway. External addition of H 2 O 2 stimulates increases in the transcription of both rsmY and rsmZ . Thus, we propose a regulatory model of the RetS‐Gac‐Rsm signalling pathway in P . syringae MB03 for the regulation of H 2 O 2 tolerance and phytopathogenicity in the host plant.

Human biomonitoring of eight trace elements in urine of residents living in rural areas along the Yangtze River, China - Yanjie Cui; Qi Zhong; Mingjun Hu; Jie Sheng; Yuanyuan Yang; Ling Liang; Xiaodong Wang; Yuwei Yang; Mengmeng Zhou; Fen Huang (Environmental Science and Pollution Research, 2017)

Micro-electrolysis/retinervus luffae-based simultaneous autotrophic and heterotrophic denitrification for low C/N wastewater treatment - Jinlong Li; Desheng Li; Yuwei Cui; Wei Xing; Shihai Deng (Environmental Science and Pollution Research, 2017)